Factors explaining postharvest loss of hot pepper under tropical conditions (2019)
Major loss of hot pepper (Capsicum chinense Jacquin) in the humid tropics is due to disease and spoilage during postharvest storage following harvest occurring when conditions are cool and damp. The study assessed socio-economic drivers of postharvest loss of hot pepper in the tropics in order to provide empirical information on the underlying causes of postharvest losses of hot pepper for efficient and sustainable hot pepper value chain policies under tropical conditions. Data were analyzed with descriptive statistics, gross margin analysis and binary logistic regression. Although Capsicum chinense had a low yield in the sub-humid region, it was profitable. Being a male, primarily engaged in farming, reduced the likelihood of high postharvest loss, while long distances and high transportation costs increased it. Technical and marketing support for smallholder farmers, especially females, could reduce postharvest loss of hot pepper.